Characteristics and mental health of psychedelic mushroom and multi-psychedelic users relative to non-psychedelic users in American adults, 2020–2021 - Abramsky-Sze, Sofia; Marseille, Elliot; Matzopoulos, Richard; Morlock, Robert; Lerer, Leonard (Frontiers in Psychiatry, 2025)
IntroductionFew population-based studies have examined associations between psychedelic use and mental health outcomes. This work describes characteristics of exclusive psychedelic mushroom use (referred to as PM use), PMs in combination with other psychedelic substances (multi-psychedelic or MP) use, and non-psychedelic use and explores mental health ratings in non-clinical settings.MethodsThis work uses cross-sectional survey data from American adults collected by Acumen Health Research Institute, including demographic characteristics, general health-related quality of life (Veterans RAND derived mental and physical health composite scores), depression (PHQ 9-item), anxiety (GAD 7-item), comorbid conditions (CCI), health resource utilization, and perceptions, knowledge, and use of psychedelics. Multivariate and descriptive statistics were used to describe participant characteristics. Correlation analysis assessed anxiety and depression scores across groups. Mean anxiety and depression scores were compared using ANOVA and Tukey’s HSD. A multivariate linear regression model controlling for past-year depression, past-year anxiety, age, region, ethnicity, sex, educational attainment, employment, and psychedelic use predicted mental health composite scores (MCS).ResultsOf the 6,869 participants included in the dataset, 256 (3.7%) reported using psychedelics in the last 12 months. Of those using psychedelics, 122 (47.7%) reported PM use and 134 (52.3%) reported MP use. All psychedelic users reported lower MCS and higher levels of anxiety and depression relative to non-users (those who said they had not used psychedelics in the past year). The lowest mental health scores were reported in the MP users followed by the PM users (higher MCS corresponded to better mental health). When controlling for confounding characteristics including past-year anxiety and depression, disparities in mental health scores persisted between those with any psychedelic use and the non-psychedelic group (p<0.001).ConclusionThis paper extends previous work describing the association between psychedelic use and mental health, controlling for confounding mental health factors such as comorbid anxiety and depression. These results suggest psychedelic users may have poorer mental health than their non-using counterparts in certain contexts and emphasize the need for future research in this field. Both non-adjusted and adjusted analyses demonstrate lower mental health scores for PM and MP users relative to non-psychedelic users. These differential effects highlight the need for further detailed, population-based research on the use of exclusive psilocybin and on psychedelics in combination.